Epidemiology of lung cancer in the Siberian Federal District: A retrospective observational study - L. D. Zhuikova; T. V. Polishchuk; O. A. Ananina; Yu. D. Kondrashina; G. A. Kononova; S. V. Miller; L. V. Pikalova (Кубанский научный медицинский вестник, 2024)
Background. Lung cancer has long been the most common type of cancer in the male population (16.4%). The incidence of lung cancer among women is increasing worldwide. In Russia, as of 2022 (compared to 2013), lung cancer shifted to the second place in the structure of cancer incidence among males, following prostate cancer. However, the anticipated rise in new cases of this pathology requires an analysis for evaluating and adjusting the current anti-cancer programs. Objective. To analyze the incidence rates and quality of oncological care provided for malignant neoplasms of the lung in the Siberian Federal District within 2013–2022. Methods. A retrospective observational study was conducted utilizing depersonalized data on the prevalence and structure of malignant neoplasms derived from the reports of the Siberian Federal District subjects, the Russian Federation (form No. 7 “Information on Malignant Neoplasms” and form No. 35 “Information on Patients with Malignant Neoplasms”), as well as from the Russian Federal State Statistics Service. The primary indicators of the study included the proportion of lung cancer within the structure of cancer incidence in men and women (C33.0, 34.0–C34.9 according to the ICD-10 classification), standardized incidence rates of lung cancer in men and women, age-specific incidence rates of lung cancer in men and women, by-stage distribution of the lung cancer tumor process, morphological verification, active case finding, one-year mortality, and the proportion of patients with malignant lung neoplasms who were registered for five years or more, uptake ratio of lung cancer population, ratio of one-year mortality to stage IV cases of the previous year. The calculations of standardized and age-specific incidence rates were performed using ONCOSTAT, while the quality indicators of oncological care were assessed using the Cancer Care Indicators software. Standardized incidence rates were calculated according to SEGI age standardization. Statistical analysis of qualitative indicators of medical care provided to patients with malignant neoplasms of the lung over time was conducted using linear regression analysis methods; statistical significance was evaluated at p ≤ 0.05. Results. A decrease in lung cancer incidence among men was observed in the Siberian Federal District, whereas the level of this indicator among women remained unchanged. The comparison of oncological care indicators for lung cancer patients in 2013 and in 2022 revealed several notable changes. The proportion of morphologically verified malignant neoplasms increased from 72.9% to 87.9%. The percentage of cases diagnosed at stages I-II grew from 24.2% to 29.1%, while the proportion of patients registered for five years or more increased from 37.3% to 43.4%. The uptake ratio of lung cancer population extended from 2.2 to 2.7. Conversely, the one-year mortality rate decreased from 55.2% to 47.8%, and ratio of one-year mortality to stage IV cases of the previous year diminished from 1.3 to 1.0. However, a number of advanced cases grew from 39.4% to 40.6%. Conclusion. The conducted epidemiological analysis revealed a decrease in the incidence of lung malignancies among men (from 63.9 to 57.5 cases per 100,000 population) and stagnation of the incidence rate among women (approximately 10.1 cases per 100,000 population) in the Siberian Federal District during the study period. The proportion of lung cancer within the structure of cancer incidence in men reduced from 21.5% to 17.6%. Key indicators of the quality of medical care provided to patients with lung malignancies demonstrate a positive trend; however, the proportion of cases diagnosed at stage IV appears pessimistic (40.6%). The obtained data necessitates the development and implementation of preventive measures for early diagnosis, including screening programs, as well as educational activities aimed at healthcare professionals and the general population, to promote healthy lifestyles and enhance oncological awareness.